Decrease in Operational Efficiency at PT X: Causes and Improvements with Lean Six Sigma DMAIC - Muhammad Faaiz Fadhlilah; Didit Damur Rochman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Efficiency in pharmaceutical warehousing is critical because accuracy, speed, and regulatory compliance determine overall supply chain reliability. PT X has experienced declining warehouse performance marked by rising defects, long cycle times, and significant non-value-added activities. Purpose: This study aims to analyze the causes of operational inefficiency and formulate structured improvements. Approach: Using the Lean Six Sigma DMAIC framework, the research applies waste identification, Value Stream Mapping, Cost of Poor Quality, DPMO and sigma measurement, Process Activity Mapping, and Failure Mode and Effect Analysis.The Measure stage reveals a total lead time of 4,890 minutes with only 250 minutes of value-added work (Process Cycle Efficiency = 5.11%) and sigma levels between 3.2–3.6 across eight defect types. Analyze findings indicate that waiting, motion, inventory, and defect waste dominate, with the highest risk originating from recording errors, missing items, and FIFO violations. Improvement through WMS digitalization, layout restructuring, SOP standardization, and visual management produces a more efficient future-state VSM. Conclusion: Inefficiency in PT X warehouse is systemic, rooted in human factors, work methods, and information flow. Originality: This study presents an integrated model combining Lean waste analysis and Six Sigma defect reduction as a unified framework for optimizing pharmaceutical warehouse operations.